2020
DOI: 10.1007/s43465-020-00261-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of Platelet Rich Plasma in Chronic Plantar Fasciitis: A Prospective Study

Abstract: Introduction Autologous platelet rich plasma (PRP) local injection has been recently proposed as a treatment of plantar fasciitis. The autologous PRP does not have much side effects compared to steroid injections. So far PRP injections have shown promising results in various studies. This study assessed the efficacy of a single local injection of PRP in chronic unilateral plantar fasciitis through a prospective case series. Methodology A hospital-based prospective case series of 30 unilateral plantar fasciitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…A recent prospective study of 60 cohorts conducted to investigate the functional and clinical outcome in patients with plantar fasciitis treated by autologous PRP injection, found statistically significant improvements in pain reduction and lower limb function at 12 weeks' follow-up.7 Similarly, other authors, have reported improvements in NPS and American orthopedic foot and ankle society (AOFAS) scores following local injection of platelet rich plasma. The findings of these studies are consistent with this case study [1,30,31].…”
Section: Discussionsupporting
confidence: 90%
“…A recent prospective study of 60 cohorts conducted to investigate the functional and clinical outcome in patients with plantar fasciitis treated by autologous PRP injection, found statistically significant improvements in pain reduction and lower limb function at 12 weeks' follow-up.7 Similarly, other authors, have reported improvements in NPS and American orthopedic foot and ankle society (AOFAS) scores following local injection of platelet rich plasma. The findings of these studies are consistent with this case study [1,30,31].…”
Section: Discussionsupporting
confidence: 90%
“…In patients who do not respond to first-line treatments and become chronic, various methods including CS injections, PRP injections, extracorporeal shock-wave therapy, or dry needling, may be considered. 2,4,9,10,13,14,[17][18][19][20][21][22][23][25][26][27][28]31,39 CS injections have become a popular second-line treatment method, with rapid improvement in pain scores in patients who do not respond to noninvasive conservative treatment methods. Although the efficacy of CS injection in the treatment of PF was previously thought to be due to the anti-inflammatory activity of CS; the prostaglandin-related anti-inflammatory effect of CS has become controversial after histopathologic studies revealed that PF is a degenerative condition and not an inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are numerous causes of heel pain, the most common in adults aged >40 years is plantar fasciitis (PF). 14,18 PF is bilateral in approximately 30% of the patients. A sharp pain under the heel and "start-up pain," which is more pronounced especially in the morning, are diagnostically important.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations